2012
DOI: 10.20453/rmh.v20i2.987
|View full text |Cite
|
Sign up to set email alerts
|

Prevenção de complicações nos pés de pessoas com diabetes mellitus: Proposta de cuidado

Abstract: Prevenção de complicações nos pés de pessoas com diabetes mellitus. Prevenção de complicações nos pés de pessoas com diabetes mellitus: Proposta de cuidado.Preventing feet complications in people with diabetes mellitus: A health care proposal. Ochoa-Vigo Kattia 1 , Pace Ana Emilia RESUMOObjetivo: Avaliar uma proposta de cuidado para pessoas com diabetes mellitus tipo 2 atendidas em unidades de atenção secundaria da saúde na rede pública, com ênfase na prevenção de lesão nos pés. Material e metodo: tratase de u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
4
0
7
Order By: Relevance
“…In a controlled clinical trial, conducted among Brazilian adults with 2DM, 56.4% of participants reported to examine their feet daily in the baseline evaluation. 20 In a descriptive study, 38.5% of participants reported to examine their feet every day, however, 69.2% said they did not know the importance of such care. 16 Foot care measures that stand out include daily examination, inspection of shoes before putting them on and feet hygiene with careful drying, especially in the interdigital spaces.…”
Section: Studies In Portugalmentioning
confidence: 99%
“…In a controlled clinical trial, conducted among Brazilian adults with 2DM, 56.4% of participants reported to examine their feet daily in the baseline evaluation. 20 In a descriptive study, 38.5% of participants reported to examine their feet every day, however, 69.2% said they did not know the importance of such care. 16 Foot care measures that stand out include daily examination, inspection of shoes before putting them on and feet hygiene with careful drying, especially in the interdigital spaces.…”
Section: Studies In Portugalmentioning
confidence: 99%
“…(6,7) A study conducted in a specialized service with patients with diabetes mellitus showed that over 50% of the study population had dermatological conditions conducive to the development of ulcers/lesions. (8) In general, patients with diabetes mellitus recognize the importance of foot care to avoid complications; however, self-care is not performed correctly. (9) The presence of complications can reduce motivation for self-care, in addition to patient limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that 79% (n = 50) of participants cut their toenails in this shape (22). This may be due to lack of understanding.…”
Section: (To Be Continued) (Conclusion)mentioning
confidence: 69%
“…Studies reveal that educational programs reduce the incidence of amputations by 50% (12,22). Health professionals can help educate patients and change this reality through collective interventions with groups of patients, families and the community.…”
Section: (To Be Continued) (Conclusion)mentioning
confidence: 99%